Pemanfaatan modalitas dalam pidato inspiratif: analisis retorika pidato Maudy Ayunda sebagai JUBIR G20 - Afrisyah, Misbahul; Kurniawan, Bima (Journal of Contemporary Issues in Primary Education, 2024)
This study examines Maudy Ayunda's speech as a spokesperson at the G20 Presidency event from December 1, 2021, to November 30, 2022, with the theme "Increasing tax transparency globally to overcome tax avoidance." This research employs rhetorical theory. The aim is to understand Maudy Ayunda's rhetoric when delivering a speech at the G20 forum. Data collection was conducted by watching and analyzing audio-visual articles. The research results indicate that Maudy Ayunda's language style encompasses the rhetorical theory of clarity, accuracy, and appropriateness. This is also evidenced by Maudy Ayunda's ability to construct sentences with clarity, strength, harmony adeptly, and the use of non-verbal language styles.